Termalização de qubits sujeitos à ação de reservatórios coletivos markovianos - Diniz, Emanuel Cardozo (Universidade Federal de São Carlos, 2014)
We are interested in understanding the process of Markovian thermalization in quantum systems when we have one or two qubits interacting with a quantum electromagnetic field mode, using the Rabi model, in situations where there is interaction with a reservoir modeling the environment surrounding the system. This analysis of the thermalization is based on the calculation of the eigenvalues of the Liouvillian of the Markovian master equation. We will focus mainly on situations where there is interaction with independent and collective reservoirs, for cases where the subsystems interact with reservoirs at T=0K and T >0K. We investigate situations where there is no thermalization of the system and how this may influence interesting physical properties, such as the statistical properties of the field in the ultra strong scheme using the theory of input-output and quantum correlations between qubits collectively interacting with Markovian reservoirs.
Keywords: Informação quântica; Rabi, Modelo de; Termalização; Interação da radiação com a matéria; Rabi model; Markovian master equation; Eigenvalues; Open quantum systems; Statistical photodetection and quantum correlations; CIENCIAS EXATAS E DA TERRA::FISICA